Architecture in Hawai'i : a chronological survey - Sandler, Rob. (Honululu, Hawai'i : Mutual Books, Inc., 1993)
From the simple, thatched hale to the nation's only royal palace, from humble plantation cottages to fabulous estates and resort hotels, Hawai'i's architecture is as diverse as its multi-ethnic population.
Chapter One: Early Hawai'i, AD 500-1819 -- Chapter Two: The missionary period, 1820-1850 -- Chapter Three: The monarchy period, 1851-1893 -- Chapter Four: The territorial period, 1893-1941 -- Chapter Five: Ethnic architecture, 1860-The present -- Chapter Six: The statehood period, 1941-1970 -- Chapter Seven: Contemporary architecture, 1971 and beyond -- Appendix A: Hawai'i architects, selected biographies -- Appendix B: Architectural awards -- Appendix C: American Institute of Architects in Hawai'i -- Appendix D: Historic Hawai'i Foundation.
Includes bibliographical references and index.
Keywords: ARCHITECTURE -- HAWAII -- PICTORIAL WORKS